PEMBELAJARAN BEHAVIORAL - Trinurmi, Sitti (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2022)
In learning, behaviorism is known as behavioral psychology, that is, a learning theory that is based on the idea that all behavior is obtained through conditioning. There are three types of conditioning, namely: (a) Contiguity, (b) Classical Conditioning Theory/ Classical Habituation Theory, and (c) Operant Conditioning Theory / Response Behavior Habituation Theory. These three theories suggest that learning is an observable change in behavior, which occurs through a stimulus-response accompanied by reinforcement. Behavioristic learning theory explains learning is a change in behavior that can be observed, measured, and assessed concretely. Change occurs through stimuli (stimulants) that give rise to reactive behavioral relationships (responses) based on mechanistic laws. Stimulants are nothing but the child’s learning environment, both internal and external that are the cause of learning. While the response is a result or impact, in the form of a physical reaction to a stimulant. Learning means the strengthening of bonds, associations, traits, and behavioral tendencies of the S-R (stimulus-Response). There are several approaches and models in Learning Behaviorism, namely: Attention, Tension, Production, and, Motivation. This method of behaviorism is very suitable for the acquisition of abilities that require practice and habituation containing elements such as; Speed, spontaneity, flexibility, reflexes, endurance, and so on, for example, foreign language conversation, typing, dancing, using a computer, swimming, sports and so on. This theory is also suitable to be applied to train children who still need the dominance of adult roles, like to repeat and should be familiarized, like to imitate, and are happy with forms of direct appreciation such as being given sweets or praise.